Innovation and Bureaucracy - Endang Indartuti; Agus Sukristyanto (Indonesian Association for Public Administration (IAPA), 2022)
The Society 5.0 is a concept that defines that technology and humans will coexist to improve the quality of human life sustainably. Therefore, the development of information and communications technology (ICT) has had a drastic impact on society and industry. Digital transformation generates new values and is a pillar of industrial policy in many countries around the world. state this is something innovative applied in the city of Surabaya as something smart city concept. Smart City Surabaya realized by providing fast and efficient public services which are realized through the implementation of e-government. The implementation of e-government carried out by the City of Surabaya as a form of local government innovation in the form of Surabaya Single Window (SSW). Surabaya city to implement this SSW service in every Kelurahan. The analysis method used is descriptive qualitative by using secondary data. The analysis result shows that the use of technological innovation in the service process improves the effectiveness, efficiency, and openness of the service process, especially in the permission only needs 14-30 days.